2002
DOI: 10.1046/j.0016-8025.2002.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional model of CO2transport in airspaces and mesophyll cells of a silver birch leaf

Abstract: A realistic numerical three-dimensional (3D) model was constructed to study CO 2 transport inside a birch leaf. The model included chloroplasts, palisade and spongy mesophyll cells, airspaces, stomatal opening and the leaf boundary layer. Diffusion equations for CO 2 were solved for liquid(mesophyll) and gaseous(air) phases. Simulations were made in typical ambient field conditions varying stomatal opening, photosynthetic capacity and temperature. Doubled ambient CO 2 concentration was also considered. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 25 publications
1
79
0
1
Order By: Relevance
“…Compared with models based on the circuitresistance analog, FEM can more accurately describe the interactive processes of CO 2 diffusion and photosynthetic reaction within a spatially explicit leaf geometry (Parkhurst, 1994;Aalto and Juurola, 2002;Tholen and Zhu, 2011;Ho et al, 2016). We assume that since sunflower leaves have a relatively high stomatal density and a relatively porous, isotropic mesophyll airspace network, a 1-D model accurately represents the interaction between CO 2 diffusional limitation and reactive demand.…”
Section: -D Porous Medium Fem Of Co 2 Diffusion and Photosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with models based on the circuitresistance analog, FEM can more accurately describe the interactive processes of CO 2 diffusion and photosynthetic reaction within a spatially explicit leaf geometry (Parkhurst, 1994;Aalto and Juurola, 2002;Tholen and Zhu, 2011;Ho et al, 2016). We assume that since sunflower leaves have a relatively high stomatal density and a relatively porous, isotropic mesophyll airspace network, a 1-D model accurately represents the interaction between CO 2 diffusional limitation and reactive demand.…”
Section: -D Porous Medium Fem Of Co 2 Diffusion and Photosynthesismentioning
confidence: 99%
“…Compared with models based on the circuit-resistance analog, a finite element model (FEM) can more accurately describe the interactive processes of CO 2 diffusion and photosynthetic reaction within a spatially explicit leaf geometry (Parkhurst, 1994;Aalto and Juurola, 2002;Tholen and Zhu, 2011;Ho et al, 2016). Using this model, we investigated if the spatial differences in light absorption profiles observed in sun-and shade-grown leaves could explain their photosynthetic responses to diffuse versus direct light.…”
mentioning
confidence: 99%
“…Traditionally, the r i has been divided into two major components : the intercellular air space resistance (from substomatal cavities to the cell surface) and the liquid-phase resistance (from the cell walls to the site of carboxylation). Theoretical and Atkins et al (1972aAtkins et al ( , 1972b; Price et al (1994); Peltier et al (1995); Gillon and Yakir (2000) experimental results suggested that the resistance of the intercellular air spaces is negligible in many cases (Genty et al, 1998;Aalto and Juurola, 2002;Piel et al, 2002), although it accounts for a significant portion of r i in thick, hypostomatous leaves (Parkhurst and Mott, 1990;Parkhurst, 1994). The resistances of the cell wall (25%-50%) and chloroplast envelopes (24%-76%) are considered to make major contributions to the total r i Gillon and Yakir, 2000).…”
mentioning
confidence: 99%
“…Paradoxically, this could mean that a decrease in the rate of photosynthesis results in a lower g i , instead of the other way around. In addition, the conductance approach usually considers only one dimension and therefore cannot incorporate the effects of the full 3D leaf structure on diffusion (Parkhurst, 1994;Aalto and Juurola, 2002). It remains challenging to modify biochemical models of photosynthesis with an adequate 3D description of diffusion (Farquhar et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation